Evolution of Approaches to Increase the Salt Tolerance of Crops. (4th March 2022) - Ashraf, M.; Munns, R.
Abstract: The existence of salinity stress can be traced well before the domestication of crops, but the documentation and mitigation of this menace started only 100 years ago. Due to the unavailability of appropriate equipment and lack of sophisticated techniques, the salinity appraisal of soils and crop injury at early times was done visually. Initially, the major focus of scientists was on reclamation and management of salt-affected soils to render them fit for agriculture. Later, they strived to assess the degree of salt tolerance of different plant species using growth and morphological traits as well as some fundamental physiological criteria, most importantly ion uptake, and accumulation. In the early 20th century, the idea of developing salt tolerant crops, as an alternative to soil reclamation was realized, and the terms "biological fix" or in general "biological approach" were coined. This triggered plant breeders to initiate breeding programs aimed at developing salt tolerant crop cultivars. Although conventional selection and breeding has several limitations, mainly its slowness, it has yielded many salt tolerant lines and cultivars of different crops. To speed up the crop breeding programs, a genetic engineering approach referred to as "transgenic approach" was introduced during the late 20th century. Plant biotechnologists have produced large numbers of transgenic lines of different crops however their use in developing salt tolerant cultivars is not remarkable. Furthermore, genetically modified (GM) crops are prohibited in many countries because of putative health risks and biosafety concerns. More recently, for precise editing of genomes of organisms, new molecular tools have been developed. For example, CRISPR-Cas9 is being used to precisely edit genes involved in abiotic stress tolerance, including salt tolerance. Its success in terms of developing cultivars tolerant to multiple stresses including salt stress is expected.